Analysis of cases of brucellosis in humans and molecular-biological characteristics of Brucella melitensis strains in regions of South European Russia with a high brucellosis incidence - А. А. Khachaturova; D. G. Ponomarenko; D. A. Kovalev; A. N. Germanova; D. E. Lukashevich; D. V. Rusanova; N. S. Serdyuk; O. V. Semenko; A. M. Zhirov; L. S. Katunina; А. N. Кulichenko (Журнал микробиологии, эпидемиологии и иммунобиологии, 2022)
Introduction. To improve the epidemiological surveillance of brucellosis in Russia, a detailed analysis of incidence and characteristics of Brucella melitensis strains circulating in the territories of the country where there is a persistent epizootic and epidemiological problem with brucellosis is required.